On the relevance of the 3D retinal vascular network from OCT data - Serranho, Pedro (2013)
Abnormal patterns of the retinal vascular system have been associated with several heart and cerebral diseases. However, these correlations were obtained using 2D imaging of the eye fundus, disregarding information on the third component (depth) of the vascular system. In this paper, we show that the depth component is relevant and should not be disregarded in this analysis. In this way, the relevance of the analysis of the retinal vascular network as a biometrical marker for the general health status of the individual can be increased.